The Role of Speculation in Competitive Price-Dynamics - Howitt, Peter (Review of Economic Studies, 1979)
It has been shown by Kaldor (1939, especially pp. 8-10) that the degree of price stabilizing speculation in a market depends upon two elasticities: (i) the elasticity of expected price with respect to current price, and (ii) the elasticity of speculative excess demand with respect to the difference between current and expected price. Speculation will generally stabilize the current price about the expected price, since a wide gap between the two gives rise to a counteracting pressure on the current price from the speculative excess demand. The smaller the first elasticity the smaller will be the fluctuations in the expected price resulting from fluctuations in underlying factors of supply or demand. The larger is the second elasticity the more closely will fluctuations in the current price reflect fluctuations in the expected price. Kaldor's analysis, like much of the more recent literature on speculation and stability (Friedman (1953), Telser (1959)) addresses the question of whether or not speculation will serve its traditionally cited role of ironing out some of the fluctuations in prevailing market prices that would occur in its absence. The question of speculation and stability has been phrased somewhat differently in the literature on general competitive analysis (Hicks (1939), Enthoven and Arrow (1956), Arrow and Nerlove (1958), Arrow and Hurwicz (1962), Arrow and Hahn (1971, 309-315)) where it is asked whether or not the presence of speculation makes it more likely that the process of market adjustment will converge asymptotically upon an equilibrium. In both of these branches of the literature the focus has been upon the first of Kaldor's elasticities, and the results have confirmed Kaldor's analysis. Putting the question either way, we may say (roughly) that speculation exerts a stabilizing influence if the elasticity of price expectations is less than unity, or if expectations are formed adaptively (Cagan (1956), Arrow and Nerlove (1958)), it exerts no influence on stability if the elasticity is unity, and it exerts a destabilizing influence if the elasticity exceeds unity or if expectations are formed extrapolatively (Arrow and McManus (1958)). The purpose of the present paper is to examine the importance of the second of Kaldor's elasticities for the convergence of the market adjustment process. In the context of a single market it is clear that if this elasticity is large enough the price-adjustment process will be stable, provided that the formation of expectations is not destabilizing, because, regardless of the slope of the non-speculative excess demand curve, a large enough elasticity of the speculative excess demand curve will imply a downward slope to the market excess demand curve. The central question of the present paper is whether or not the analogous result holds in the multi-market economy of general competitive analysis. The answer to this question is vital to the broader issue of the influence of speculation on stability, because the size of this elasticity can be interpreted as defining the existing degree of speculation. The characteristic feature of speculation that distinguishes it from similar activities, such as hedging or investing, that also may be influenced by future price expectations, is that speculation is primarily motivated by the expectation of capital gain, not by the desire to consume or otherwise transform commodities, to avoid risk, or to